Crime and punishment: An economic analysis of illegal fishing - Coelho, Manuel Pacheco (2009)
Public enforcement of law is an obvious important theoretical and empirical subject for Social Sciences. First literature dates from eighteen century: Montesquieu, Beccaria and Bentham. After the sophisticated analysis of Bentham, enforcement subject “lay essentially dormant in economic scholarship”, until BECKER (1968) article, “Crime and Punishment: An Economic Approach”. In Fisheries Economics, this can be seen as an externality arising when exclusive property rights are absent, and that absence depends, particularly, on the costs of defining and enforcing exclusivity. Efficiency considerations don't dictate, only by themselves, the choice of a certain property rights regime. In “common property" the realignment of the property rights can have a very high or even prohibitive cost. This model combines standard Economics of Fisheries analysis (Gordon/Schaefer model) with Becker’s Theory of “Crime and Punishment”. The conclusions are used to discuss the design and reform of the control and monitoring regime of the Common Fisheries Policy.